Uncinate fasciculus microstructural organisation and emotion recognition in schizophrenia: controlling for hit rate bias - Stevens, Matthew; Ní Mhurchú, Síle; Corley, Emma; Egan, Ciara; Hallahan, Brian; McDonald, Colm; Donohoe, Gary; Burke, Tom (Frontiers in Behavioral Neuroscience, 2024)
Schizophrenia (SCZ) is a complex neurodevelopmental disorder characterized by functional and structural brain dysconnectivity and disturbances in perception, cognition, emotion, and social functioning. In the present study, we investigated whether microstructural organization of the uncinate fasciculus (UF) was associated with emotion recognition performance.Additionally, we investigated the usefulness of an unbiased hit-rate (UHR) score to control for response biases (i.e., participant guessing) during an emotion recognition task (ERT). Fiftyeight individuals diagnosed with SCZ were included. The CANTAB ERT was used to measure social cognition. We found that the microstructural organization of the UF was significantly correlated with physical neglect, and emotion recognition outcomes. Furthermore, we found that the UHR score was more sensitive to ERT subscale emotion items than the standard HR score. Finally, given the association between childhood trauma (in particular childhood neglect) and social cognition in schizophrenia, a mediation analysis found evidence that microstructural alterations of the UF mediated an association Childhood trauma and social cognitive performance, suggesting that early life adversity impacts both brain development and social cognitive outcomes for people with SCZ.